Theory and Practice/Fighting the Recipe Cookbooks - Pavlů, Dušan (Communication Today, 2025)
In the global world, new paradigms of social development are constantly established. Universities are at an intersection of two interests in the bachelor’s degrees of education: the students are demanding more practical experience, but the educators condition the acquisition of practical skills also by a necessary level of understanding the phenomena through the necessary amount of theoretical knowledge of the domain. This paper points to this conﬂict of interest against the background of some of the global researches that unequivocally point to a higher theoretical education of staff, which allows implementing hands-on activities with a high degree of efﬁciency. It indicates a variety of approaches and views of the managerial and marketing theory today commenting on current phenomena in social development and at the same time presenting the writer´s thought on possible directions of university study orientation in the ﬁeld: marketing communications.